Experimental Investigation on Strengthening of Zea Mays Root Fibres for Biodegradable Composite Materials Using Potassium Permanganate Treatment - Saavedra-Flores, E (Nature Research, 2024)
Humans are the only species who generate waste materials that cannot be broken down by natural processes. The ideal solution to this waste problem would be to employ only compostable materials. Biodegradable materials play a key role in creating a safer and greener world. Biodegradability is the gift that keeps on giving, in the sense of creating an Earth worth living. The future is thus best served by green energy, sustainability, and renewable resources. To realize such goals, waste should be considered as a valuable resource. In this context, Zea mays (Zm) root fibres, which are normally considered as agricultural waste, can be used as reinforcing substances in polymer matrices to produce structural composite materials. Before being used in composites, such fibres must be analysed for their physical properties. Chemical treatments can be employed to improve the structural quality of fibres, and the changes due to such modification can be analysed. Therefore, the current work examines the effect of permanganate treatment on the surface properties of Zm fibres. The raw and potassium permanganate-treated samples were assayed for various properties. Physical analysis of the fibre samples yielded details concerning the physical aspects of the fibres. The thermal conductivity and moisture absorption behaviour of the samples were analysed. Chemical analysis was employed to characterize the composition of both treated and untreated samples. p-XRD was employed to examine the crystalline nature of the Zm fibres. Numerous functional groups present in each sample were analysed by FTIR. Thermogravimetric analysis was used to determine the thermal stability of Zm fibres. Elemental analysis (CHNS and EDS) was used to determine the elemental concentrations of both raw and treated samples. The surface alterations of Zm fibres brought on by treatment were described using SEM analysis. The characteristics of Zm roots and the changes in quality due to treatment were reviewed, and there were noticeable effects due to the treatment. Both samples would have applications in various fields, and each could be used as a potential reinforcing material in the production of efficient bio-composites. © The Author(s) 2024.